IMPACT OF LEADERSHIP IN CAMBODIAN HIGHER EDUCATION THROUGH DIGITALIZATION - Dr. Ros Paradise; Dr. Polla Prak (JF Publisher, 2024)
Digitalization has been identified as a key factor for Cambodia to meet its vision 2030/2050. To achieve these visions, higher education is a powerful tool to develop human capital for national/regional competitiveness in the digital era. Very few studies have been conducted on how Cambodian higher education leaders do to prepare for this coming era of digitalization. This study employed a qualitative method using open-ended question. Forty-five key stakeholders in Cambodian higher education sector and policy makers voluntarily participated in the study. They were selected using Purposive and Snowball sampling techniques. Data were collected through the in-depth interviews to explore the participants’ perceptions of an impact on leadership related to higher education in the digital era. The study also seeks to understand the digitalization, key challenges, current practices, and strategies to deal with it. Qualitative methods were used for data analysis and interpretation. The results of the study show that there are many factors that higher education leaders need to explore, especially, strategies and prioritized areas. Findings from the study significantly contribute to the positive changes in higher education sector, especially the preparation and leading Cambodian higher education to achieve the policies of the Royal Government of Cambodia, especially the vision 2030/2050.